If X-3=-5 then X= ( ) A)2 B)-2 C)8 D)-8
Answers
Answered by
0
Answer:
-2
Step-by-step explanation:
x-3=-5
x=-5+3=-2
Answered by
0
Answer:
B) -2
Step-by-step explanation:
x-3=-5
x=-5+3
x=-2
whenever we bring a no o expression from one side to the other its sign changes from + to - , - to + , × to ÷, ÷ to ×
Similar questions
Chemistry,
2 months ago
Computer Science,
2 months ago
Math,
2 months ago
English,
4 months ago
Science,
4 months ago
Environmental Sciences,
11 months ago
Math,
11 months ago